Pemberdayaan Kewirausahaan Perempuan HWK (Himpunan Wanita Karya) Desa Kalirandu melalui Edukasi dan Pendampingan - Priatiningsih, Dian; Mardayanti, Mella; Ulum, E. Akhmad Samsul; Syafnita, Syafnita; Fachrur, M. Maulidin; Taruna, M. Sigit (Medan Resource Center, 2025)
Women's entrepreneurship plays an important role in improving family welfare and empowering the rural economy. However, limited access to information, training, and mentoring often hinders rural women from developing their business potential. This community service activity aims to empower members of the Himpunan Wanita Karya (HWK) in Kalirandu Village, Petarukan Subdistrict, Pemalang Regency through entrepreneurship education and mentoring programs. The implementation methods include training in business management, basic financial management, product innovation, and digital marketing strategies. In addition, intensive mentoring was provided in the production, packaging, and promotion processes of local products based on village potential. The results of the activity showed increased knowledge and skills among HWK members in running their businesses in a more planned and sustainable manner. Participants also showed greater motivation to develop independent businesses and collaborate with fellow members in product marketing. This activity had a positive impact on enhancing women's entrepreneurial capacity in the village and made a real contribution to family economic independence. Program sustainability will be ensured through regular monitoring and the establishment of community-based joint business groups (KUB). With a participatory and sustainable approach, this program is expected to become a model for rural women’s empowerment that can be replicated in other regions with similar characteristics.